Fetal cervical teratoma giant: a case report - admin, admin (2018)
Fetal cervical tumors are infrequent findings and most of them are not diagnosed prenatally. The objective of this paper is to present and discuss in a critical way the diagnosis, evaluation and post natal evolution of a giant fetal cervical tumor case, also of his differential diagnosis.